STRESS, TRAUMA AND POST-TRAUMATIC STRESS DISORDER (PTSD) (Annual of the Faculty of Philosophy in Skopje, 2023)
In this paper, we will attempt to describe an integrative model that links stress, trauma, and post-traumatic health disorders through biological, psychological, and behavioral mechanisms of influence. Each of these phenomena has its specificities but also shares common characteristics (sources, symptoms, and consequences) related to health and an individual’s functioning. Prolonged stress and sudden experiences can lead to trauma, and repeated experiences of trauma over time can result in the development of post-traumatic stress disorder (PTSD). This key mechanism illustrates how long-term stress and trauma can lead to severe health impairment.A review of the literature on this topic, along with our many years of experience and research in these areas, reveals that the majority of authors in their research primarily focus on one of these topics, usually stress. There are fewer studies that provide a comprehensive representation of both stress and trauma. We have not come across any research that unifies all three topics in their presentation, highlighting the common elements as well as the specificities and differences.The aim of this paper is to demonstrate, through an integrative approach, the combined impact of these three phenomena on health and an individual’s functioning. First, we will describe each of these phenomena along with their respective specifications. Finally, we will attempt to integrate the knowledge of physiological and psychological mechanisms for dealing with stress, trauma, and post-traumatic stress disorder. Although challenging, we will also touch upon prevention strategies towards the end.
Keywords: stress; trauma and post-traumatic stress disorder - PTSD